Optimization Of Solar Panel Usage In Grid-Connected Hybrid Energy Systems Using Fuzzy Method - Maizana, Dina; Muhathir, Muhathir; Satria, Habib; Mungkin, Moranaim; Siregar, Muhammad Fadlan; Yahya, Yanawati Binti (P3M Politeknik Negeri Banjarmasin, 2024)
The hybrid grid-connected power generation system combines solar power, wind power, and the PLN grid to meet the electricity demands of facilities such as schools, laboratories, mosques, and kindergartens at MTs Parmiyatu Wassa'adah School. Due to insufficient wind speed below the turbine's operational threshold, wind turbines cannot contribute to electricity generation, making solar power the primary energy source. Solar power capacity is crucial for meeting the electricity needs of these facilities. This study applies the Fuzzy method to analyze the optimal utilization of solar panels in a grid-connected hybrid system for electricity demand. Simulation results indicate three levels of solar panel utilization, with the most optimal performance achieved when school electricity usage is low, and additional loads are minimized.